Intrauterine exposure to bisphenol A promotes different effects in both neonatal and adult prostate of male and female gerbils (Meriones unguiculatus) - Rodríguez, Daniel A. O.; Lima, Rodrigo F. de; Campos, Mônica S. [UNESP]; Costa, Janaína R.; Biancardi, Manoel F.; Marques, Mara R.; Taboga, Sebastião R. [UNESP]; Santos, Fernanda C. A. (Wiley-Blackwell, 2015)
Substances that mimic endogenous hormones may alter the cell signaling that govern prostate development and predispose it to developing lesions in adult and senile life. Bisphenol A is able to mimic estrogens, and studies have demonstrated that low levels of exposure to this compound have caused alterations during prostate development. The aim of this study was to describe the prostate development in both male and female neonatal gerbils in normal conditions and under exposure to BPA during intrauterine life, and also to analyze whether the effects of intrauterine exposure to BPA remain in adulthood. Morphological, stereological, three-dimensional reconstruction, and immunohistochemical methods were employed. The results demonstrated that in 1-day-old normal gerbils, the female paraurethral glands and the male ventral lobe are morphologically similar, although its tissue components-epithelial buds (EB), periurethral mesenchyme (PeM), paraurethral mesenchyme (PaM) or ventral mesenchymal pad (VMP), and smooth muscle (SM)-have presented different immunolabeling pattern for androgen receptor (AR), and for proliferating cell nuclear antigen (PCNA). Moreover, we observed a differential response of male and female prostate to intrauterine BPA exposure. In 1-day-old males, the intrauterine exposure to BPA caused a decrease of AR-positive cells in the PeM and SM, and a decrease of the proliferative status in the EB. In contrast, no morphological alterations were observed in ventral prostate of adult males. In 1-day-old females, BPA exposure promoted an increase of estrogen receptor alpha (ERα) positive cells in PeM and PaM, a decrease of AR-positive cells in EB and PeM, besides a reduction of cell proliferation in EB. Additionally, the adult female prostate of BPA-exposed animals presented an increase of AR- and PCNA-positive cells. These results suggest that the prostate of female gerbils were more susceptible to the intrauterine BPA effects, since they became more proliferative in adult life. © 2015 Wiley Periodicals, Inc. Environ Toxicol, 2015.
Keywords: Endocrine disruptors; Hormone receptors; Intrauterine growth; Morphology; Prostate development